Virtual surgical planning and 3D printing in neocondyle regeneration after mandibular condyle reconstruction with microvascular fibula free flap: Report of two clinical cases - Loi, Nguyen Hong; Khanh, Nguyen Van; Phu, Ho Man Truong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Mandibular condyle reconstruction remains a challenging procedure because it requires restoration of mandibular continuity, occlusion, facial symmetry, and temporomandibular joint function. Virtual surgical planning (VSP) and three-dimensional (3D) printing may improve the precision of fibula free flap reconstruction and facilitate accurate neocondyle positioning. Case presentation: We report two female patients who underwent segmental mandibulectomy involving the condylar region followed by microvascular fibula free flap reconstruction assisted by VSP and 3D printing. The first patient was a 35-year-old woman with fibrous dysplasia and an approximately 13-cm mandibular defect. A three-segment fibula reconstruction was performed, with preservation of the articular disc and passive positioning of the distal fibular end as a neocondyle. The second patient was a 65-year-old woman with unicystic ameloblastoma and an approximately 11-cm mandibular defect. A two-segment fibula reconstruction was performed, and the distal fibular end was positioned approximately 3 mm below the glenoid fossa. Operative time was 5.5 hours and 5 hours, respectively. During follow-up at 3, 6, 12, and 18 months, both patients showed stable mandibular contour, acceptable occlusion, satisfactory mouth opening, and no temporomandibular joint ankylosis or tumor recurrence. Serial imaging demonstrated adaptive remodeling of the distal fibular end into a neocondyle-like structure, with bone growth mainly directed along the lateral pterygoid traction vector and toward the glenoid fossa. The younger patient showed more pronounced remodeling than the older patient. Conclusion: VSP and 3D printing enabled accurate planning and transfer of fibula osteotomies, supported passive neocondyle positioning, and contributed to stable functional reconstruction after mandibular condyle resection. Neocondyle regeneration after fibula free flap reconstruction appears to be functionally driven by muscle traction and adaptive loading, although larger studies with quantitative 3D analysis are needed to confirm these findings.